Towards a Theory of Central Bank Liquidity Management - Ulrich Bindseil (Kredit und Kapital, 2000)
Elemente einer Theorie der Liquiditätssteuerung von Notenbanken Die "Liquiditätssteuerung" einer Notenbank wird definiert als der Rahmen, die Instrumente und Regeln, die die Notenbank zur Steuerung des Angebots an Bankreserven, und damit zur Steuerung von deren Preis (d.h. insb. des Tagesgeldsatzes) einsetzt. Der vorliegende Beitrag diskutiert einige Elemente einer Theorie der Liquiditätssteuerung. Die Zeitstruktur bei der Erfüllung der Reservehaltung wird als Schlüsselgröße des Rahmens der Liquiditätssteuerung identifiziert. Anschließend wird die Rolle des Optimierungskalküls der Banken innerhalb der Reserveerfüllungsperiode verdeutlicht und das Konzept der "Strategie" der Liquiditätssteuerung eingeführt. Zuletzt werden die Grundzüge einer normativen Theorie der Liquiditätssteuerung entworfen und mit einem einfachen Beispiel illustriert. – – The "liquidity management" of a central bank is defined as the framework, set of instruments and rules the central bank uses in steering the amount of bank reserves in order to control their price (i.e. short term interest rates) in consistency with its ultimate goals (e.g. price stability). This paper discusses the basic tools of a tentative theory of liquidity management. The time-structure of fulfilling reserve requirements is identified as the crucial dimension of the "framework" for liquidity management. The paper then gives an overview of key elements explaining how the optimisation behaviour of banks shapes overnight rates in a system with reserve requirements and averaging. The paper continues by specifying the concept of "liquidity management strategy" and by providing examples of such strategies. Finally, based on the preceding elements, it outlines the approach that a normative theory of liquidity management could follow and provides a basic example as illustration. (JEL E52)
Keywords: E52; 330